Rare cause of red eyes: Cogan's syndrome - Shipra Gulati; Rishikesh Dessai; Kunal Chawla; Neeraj Jain (Current Medicine Research and Practice, 2023)
A 74-year-old hypertensive male presented with redness of both the eyes, bilateral hearing loss and on and off fever since 1 month. A diagnosis of Cogan's syndrome was made, and treatment with systemic steroids and immune-suppression led to complete reversion of his symptoms, red eyes and hearing loss.